Morphological and Morphometrical Studies on the Tibia and Fibula of Tiger (Panthera tigris). - Tomar M P S; Vaish R; Archana K (Indian Journal of Veterinary Anatomy, 2026)
The study reports gross anatomical details of the tibiaand fibula of tiger. Bones of five adult tigers of either sex were studied out of which two procured from Department of Wildlife Health and management and three from Department of Veterinary Anatomy and Histology, College of Veterinary Science and Animal Husbandry Madhya Pradesh Pashu chikitsa Vigyan Vishwavidyalaya (NDVSU), Jabalpur (M.P.).The tibia was the larger of the two bones in the leg region. Tibia was long, prismatic and distinctly curved at its upper two third and cylindrical at its lower third. The mean circumference of the shaft was 16.72 + 0.29 cm, 10.06 + 0.17 cm and 10.18 + 0.18 cm at its upper, middle and lower parts, respectively.The proximal extremity presented two condyles and a tibial tuberosity. The distal  extremity showed two cranio-caudally directed oblique articular groove of which the medial was deeper than the lateral. The fibula was very thin and flattened mediolaterally and curved distally. It presented a shaft and two extremities. It weighed 28.52 + 0.46 g and was 29.26 + 0.28 cm in length. The shaft was thin and cylindrical in the proximal third and flat in the lower two third. However, it differed nonsignificantly in morphometry.